Creating a Single South African Keyboard Layout to Promote Language - Bailey, Dwayne (Lexikos, 2007)
Abstract: In this case study, a description is given of a keyboard layout designed to address the input needs of South African languages, specifically Venda, a language which would otherwise be impossible to type on a computer. In creating this keyboard, the designer, Translate.org.za, uses a practical intervention that transforms technology from a means harming a language into one ensuring the creation and preservation of good language resources for minority languages. The study first looks at the implications and consequences of this missing keyboard, and then follows the process from conception, strategy, research and design to the final user response. Not only are problems such as researching the orthographies, key placement and keyboard input options examined, but strategic objectives such as ensuring its wide adoption and creating a multilingual keyboard for all South African languages are also discussed. The result is a keyboard that furthers multilingualism and ensures the capturing of good data for future research. Finally it is a tool helping to boost and bolster the vitality of a language.